2015
DOI: 10.1007/s10827-015-0574-4
|View full text |Cite
|
Sign up to set email alerts
|

Networks that learn the precise timing of event sequences

Abstract: Neuronal circuits can learn and replay firing patterns evoked by sequences of sensory stimuli. After training, a brief cue can trigger a spatiotemporal pattern of neural activity similar to that evoked by a learned stimulus sequence. Network models show that such sequence learning can occur through the shaping of feedforward excitatory connectivity via long term plasticity. Previous models describe how event order can be learned, but they typically do not explain how precise timing can be recalled. We propose … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 94 publications
1
25
0
Order By: Relevance
“…RNNs successfully solve machine learning tasks, such as natural language processing [3] and translation, [4] and composing music, [5] to name only a few domains. In particular, much of this success has been achieved by the use of recurrent networks of LSTM (long short-term memory) cells, first introduced by Hochreiter and Schmidhuber in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…RNNs successfully solve machine learning tasks, such as natural language processing [3] and translation, [4] and composing music, [5] to name only a few domains. In particular, much of this success has been achieved by the use of recurrent networks of LSTM (long short-term memory) cells, first introduced by Hochreiter and Schmidhuber in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Previous models have shown that neural activity sequences can emerge from initially unstructured networks of excitatory neurons via spike-timing-dependent plasticity (STDP) (Fiete et al, 2010; Veliz-Cuba et al, 2015; Ravid Tannenbaum and Burak, 2016). Compared with these earlier works, our model has the advantage of being able to dynamically adjust the speed of the activity sequence, as shown in Figure 4e ( cf .…”
Section: Resultsmentioning
confidence: 99%
“…however Refs. [Veliz-Cuba et al, 2015; Pehlevan et al, 2015; Tristan et al, 2014], where some temporal rescaling in activity patterns has been obtained using distinct mechanisms). In addition, our model does not require the assumption of heterosynaptic competition limiting the summed synaptic weights into and out of each unit, as in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In models with supervised plasticity rules, the synapses are updated according the activity of the network and an error signal that carries information about the difference between the current network dynamics and the one that it is expected to learn by the network (Sussillo and Abbott, 2009;Laje and Buonomano, 2013;Memmesheimer et al, 2014;Rajan et al, 2016). In models with unsupervised plasticity rules, sequential dynamics is shaped by external stimulation without an error signal (Jun and Jin, 2007;Liu and Buonomano, 2009;Fiete et al, 2010;Waddington et al, 2012;Okubo et al, 2015;Veliz-Cuba et al, 2015). In those models SA is generated spontaneously, and the temporal statistics of the stimulation shapes the specific timing of the sequences.…”
Section: Introductionmentioning
confidence: 99%